Linear sweep voltammetry with non-triangular waveforms at a microdisc electrode - Uchida, Y; Kätelhön, E; Compton, R (Elsevier, 2018)
The voltammetry of an electrochemically reversible reaction at a microdisc electrode is investigated for a semi-circular potential waveform. At the midpoint of the potential window an instantaneous infinite scan rate is observed while relatively slow scan rates are seen in other areas of the wave. As a result, the method exhibits a much higher current response than the conventional triangular potential wave thus allowing qualitative analysis of a species with significantly greater ease, particularly at low analyte concentrations in solutions comprising multiple analytes.